THE TRANSFORMATIVE IMPACT OF ARTIFICIAL INTELLIGENCE ON BARIATRIC SURGERY: ENHANCING PATIENT OUTCOMES, SURGICAL PRECISION, AND POSTOPERATIVE CARE - Cabral, Nádia Oliveira; Bento, Rodolpho Bicalho; Barreto, Ana Julia Nassar; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Bariatric surgery has become a leading intervention for severe obesity, markedly improving weight loss, resolving comorbidities, and enhancing quality of life. However, the complexity of these procedures necessitates comprehensive patient management to optimize outcomes. Recent artificial intelligence (AI) advancements present innovative solutions that can significantly transform bariatric surgery. This narrative review examines the potential of AI to enhance patient outcomes, improve surgical precision, and streamline postoperative care, highlighting its role in revolutionizing bariatric practices and addressing the challenges faced in this field.